Continuous glucose monitoring (Dexcom g6) in people with diabetes after kidney transplantation - Zuzanna Jakubowska; Jolanta Małyszko (Renal Failure)
Objectives Use of continuous glucose monitoring-CGM in patients on kidney replacement therapy including kidney transplant recipients, may improve glycemic control and detection of hypoglycemia. However, studies in this population in particular in kidney transplant recipients are very limited.Methods The study aimed to evaluate glycemic profiles using the Dexcom G6 CGM system for 30 d a personal smartphone in people with diabetes after kidney transplantation and to assess the impact of monthly use of the CGM system on glycemic control and quality of life in this group.Results Over 8 months, 9 people after kidney transplantation were included in the study (7 women, median age 57 years), 8 people with new-onset diabetes after transplantation (NODAT), and 1 person with diabetes mellitus type 1. The time since kidney transplantation in each of the study participants was less than 2 years. In 7 people with NODAT, the time in range was above 70%. In all study participants, hyperglycemia was observed mainly in the afternoon (2–6 pm). In some patients, pressure-induced sensor attenuations (PISAs) were noted. There was no effect of the use of Dexcom G6 on the HbA1c value. There was no impact of the use of the Dexcom G6 system on the perception of overall quality of life, but monthly use had a positive impact on the perception of the quality of health.Conclusions CGM systems seem to be a promising method for assessing glycemic control in people with diabetes after kidney transplantation. More extensive research is needed to assess safety and usefulness in everyday practice.